Factors That Affect the Work Stress of Nurses in the Inpatient Room at RSUD Dr. Rasidin Padang - Mu'awanah; Suhardono (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
Work stress is a frequent problem faced by health workers, especially nurses, which can adversely affect their performance and well-being. Excessive stress can cause physical and mental fatigue, reduce the quality of health care, and increase the number of absenteeism and turnover of nurses. Purpose: the study aims to identify factors that affect the work stress of nurses in the hospital inpatient dr. Rasidin Padang. Methods: the study used quantitative descriptive design with cross-sectional approach. The samples used were 45 nurses working in the inpatient room, taken by purposive sampling technique. Data collection was conducted using questionnaires that measure the factors that cause work stress, namely workload, organizational factors, social support, and individual factors. Data analysis was conducted using descriptive statistical analysis, frequency test, and Spearman correlation test to see the relationship between variables. Results: the results showed that most nurses in the hospital inpatient dr. Rasidin Padang reported moderate levels of work stress (44.44%), with 33.33% reporting high work stress and 22.22% low work stress. Bivariate analysis revealed that high workload had a significant positive association with work stress (r = 0.632, p < 0.01), while better social support was associated with lower levels of work stress (r = -0.408, p < 0.05). In addition, individual factors associated with personal stress also showed a significant positive association with occupational stress (r = 0.653, p < 0.01). Conclusion: inpatient nursing work stress can be reduced by managing the factors that influence it more effectively.